Preliminary development and testing of an open-path hydrocarbon sensor for oil and gas facility monitoring - Farris, Betsy M., author; Yalin, Azer P., advisor; Fischer, Emily V., committee member; Jathar, Shantanu H., committee member (Colorado State University. Libraries, 2019)
We developed an open-path laser absorption sensor for detection of unspeciated hydrocarbons for oil and gas production facility fence line monitoring. Such sensors can aid in maintaining air quality standards by quantifying greenhouse gas emissions and detecting emissions that cause adverse health effects. Our initial design employs a single-path detection system, though future implementations may use multiple paths for large-scale facility monitoring. The sensor uses a compact mid-infrared laser source in the spectral region of ~3.3 µm to measure absorption of several hydrocarbon species and is intended for open-paths of ~100 m to 1 km. Spectral simulations show that for typical conditions the hydrocarbons cause a transmission reduction of ~10% allowing for a robust measurement. The initial prototype system uses a helium-neon (He:Ne) laser at 3.391 µm for which signal contributions from methane and non-methane hydrocarbons are comparable. Closed-cell tests were performed with diluted methane (~150-250 ppm) to validate the transmission signals and showed good agreement with expected (calculated) values to within ~10%. The system employs a reference leg, with a 2nd detector (near the source), to normalize for laser power fluctuations. For improved signal-to-noise, particularly for detection of small concentrations and transmission changes, we employ phase-sensitive detection with a mechanical chopper and software based lock-in amplifier. This detection scheme, when employed in the field, allows measurement of transmission signals with stability <0.5% (based on coefficient of variation over 60 s). The portable field sensor system uses two refractive telescopes (2" diameter optics), a transmitter and receiver co-located on a mobile optical breadboard, and a reflector dictating the pathlength. We performed initial tests with pathlengths up to ~25 m (one way), though the design should allow paths in excess of 100 m. Methane was released for initial field tests at known flow rates near the center of the beam path. Transmission signals in agreement with expectations (given uncertainties in the wind and plume dispersion) were observed. The system should allow detection of leaks (emissions) for mass flows as low as ~0.1 g/s of methane (or equivalent optical signal from other species resulting in a 1% change in signal) for the case where the source is ~150 m from the beam path and under typical atmospheric conditions. Recommendations for future modifications are provided based on potential shortcomings identified by initial field testing. Initial field testing also proved that this technology could be a viable low-cost solution for hydrocarbon detection.
Keywords: hydrocarbons; oil and gas; VOC; laser sensor; fence line measurement; open path